2012
DOI: 10.3109/00365521.2012.685758
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent manually controlled versus continuous infusion of propofol for deep sedation during interventional endoscopy: A prospective randomized trial

Abstract: Both sedation regimens allow nearly identical good controllability of propofol sedation. However, recovery time was significantly slower and hypotension was tended to occur more often in the perfusor group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
3
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 36 publications
4
29
3
4
Order By: Relevance
“…Continuous infusion via a perfusor pump may be preferable to take advantage of propofol pharmacokinetics in order to maintain a constant sedation level, so that we can avoid the peaks and valleys of the propofol plasma concentration once achieved the desired target of sedation and minimizing the risk of propofol overdosing as well. In this regard, NAAP through PCI may fit especially with endoscopic procedures longer than colonoscopy, such as endoscopic ultrasonography or endoscopic retrograde cholangiopancreatography, as recently shown (15). Of note, similar results than ours were obtained in this study when comparing both ways of administering propofol, titrated to deep sedation, for interventional endoscopy.…”
Section: Discussionsupporting
confidence: 73%
“…Continuous infusion via a perfusor pump may be preferable to take advantage of propofol pharmacokinetics in order to maintain a constant sedation level, so that we can avoid the peaks and valleys of the propofol plasma concentration once achieved the desired target of sedation and minimizing the risk of propofol overdosing as well. In this regard, NAAP through PCI may fit especially with endoscopic procedures longer than colonoscopy, such as endoscopic ultrasonography or endoscopic retrograde cholangiopancreatography, as recently shown (15). Of note, similar results than ours were obtained in this study when comparing both ways of administering propofol, titrated to deep sedation, for interventional endoscopy.…”
Section: Discussionsupporting
confidence: 73%
“…Our results are in line with the results by González-Santiago et al [20] and Riphaus et al [21]. The aim of those studies was to investigate safety, quality of sedation, and recovery time from propofol sedation.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, the satisfaction of the patients, nurses, and endoscopists with the sedation has not been studied for the different sedation regimens. Riphaus et al [21] showed comparable satisfaction rates for patients, nurses, and endoscopists in both groups. A possible intention to achieve a more sustained sedative effect by maintaining a preset concentration of propofol in the blood or brain, providing a higher patient satisfaction with the procedural sedation was not approved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The published protocols for continuous propofol infusion states are 2 to 5 mg/kg/hr (or 100 to 200 mg/hr), sometimes with an initial 0.25 to 0.5 mg/kg bolus 9,21,22,23. Although continuous infusion of propofol by a pump is widely used in anesthesia practice and the pumps are easily programmed, most nonanesthesiologists prefer the flexibility of the bolus approach 9,21…”
Section: Sedation Regimens For Endoscopists In Actual Practicementioning
confidence: 99%